KEMAMPUAN BERPIKIR KREATIF TERHADAP PEMECAHAN MASALAH - Selvi Monisa; Bistari Bistari; Dona Fitriawan (IKIP Siliwangi, 2023)
This study aims to determine and describe the ability to think creatively mathematically on solving problems of a two-variable linear equation system at SMK PGRI Pontianak. The method used in this study is a qualitative description. Sources of data in this study were students of class X SMK PGRI Pontianak. The instrument used to conduct the research is a mathematical creative thinking ability test for solving SPLDV problems, namely the fluency indicator is included in the low category with a score of 38% of 13 participants, the flexibility indicator is in the medium category with a number of 69% of 13 participants, and the original indicator is in the low category with a rate of 46% from 13 participants. Thus, it is concluded that the creative thinking ability of class X is at level 0 or not creative thinking.